Health-related Quality of Life Among Adult Migrant Garment Workers in Dhaka City (Bangladesh Medical Journal, 2014)
The objective of this cross-sectional study was to assess the health-related quality of life among adult migrant garment workers (age 18-59 years) in Dhaka city. The study was conducted with 400 workers for quantitative research, and two health care service providers for qualitative research. Data were collected during February to March 2009. Data were collected by face-to-face interviews using a constructed pre-tested questionnaire adapted from WHOQOL-BREF. Data were analyzed by applying descriptive statistics (frequency, percentage, mean, standard deviation, range and median) and inferential statistics (unpaired ttest and oneway ANOVA) to examine the relationship between health-related quality of life and socio-demographic characteristics, living and working conditions, and accessibility to health care services. Statistical significance was set as p